PENINGKATAN KEMAMPUAN MUHADATSAH SISWA MELALUI METODE AUDIO-LINGUAL PADA SISWA KELAS XI DI MA DARUSSALAM LAMPUNG SELATAN - Nur, Robiyah; Darmawan, Alim Syahid; Zulhannan; Fauziah, Asti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study examines the application of the Audio-Lingual Method (ALM) to improve Muhadatsah (Arabic speaking) skills in second-year students at MA Darussalam, South Lampung. Utilizing a Classroom Action Research (CAR) design, the study was conducted in two cycles, incorporating tests, observations, and documentation as the primary data collection methods. Quantitative data analysis revealed a significant improvement in students' Muhadatsah abilities, particularly in pronunciation, fluency, and vocabulary usage, as measured in pre- and post-tests. The results indicate that ALM, with its emphasis on repetitive drills and speaking exercises, effectively enhances Arabic speaking skills, making it a valuable approach for Arabic language education.